Transcriptomic Profile Analysis of Brain Tissue in the Absence of Functional TRPM8 Calcium Channel - Erick B. Saldes; Alexandra Erdmier; Jai Velpula; Timothy E. Koeltzow; Michael X. Zhu; Swapna Asuthkar (Biomedicines)
Background/Objectives: Transient Receptor Potential Melastatin 8 (TRPM8) is a non-selective, Ca2+-permeable cation channel involved in thermoregulation and other physiological processes, such as basal tear secretion, cell differentiation, and insulin homeostasis. The activation and deactivation of TRPM8 occur through genetic modifications, channel interactions, and signaling cascades. Recent evidence suggests a significant role of TRPM8 in the hypothalamus and amygdala related to pain sensation and sexual behavior. Notably, TRPM8 has been implicated in neuropathic pain, migraines, and neurodegenerative diseases such as Parkinson’s disease. Our laboratory has identified testosterone as a high-affinity ligand of TRPM8. TRPM8 deficiency appears to influence behavioral traits in mice, like increased aggression and deficits in sexual satiety. Here, we aim to explore the pathways altered in brain tissues of TRPM8-deficient mice using the expression and methylation profiles of messenger RNA (mRNA) and long non-coding RNA (lncRNA). Specifically, we focused on brain regions integral to behavioral and hormonal control, including the olfactory bulb, hypothalamus, amygdala, and insula. Methods: RNA was isolated and purified for microarray analysis collected from male wild-type and TRPM8 knockout mice. Results: We identified various differentially expressed genes tied to multiple signaling pathways. Among them, the androgen–estrogen receptor (AR-ER) pathway, steroidogenesis pathway, sexual reward pathway, and cocaine reward pathway are particularly worth noting. Conclusions: These results should bridge the existing gaps in the knowledge regarding TRPM8 and inform potential targets for future studies to elucidate its role in the behavior changes and pathology of the diseases associated with TRPM8 activity.